Online Service Policy Reform for Building Permits at the Department of Capital Investment and One-Door Integrated Services of Boyolali District - Andan Hafsari Mukminati; Andina Elok Puri Maharani (International Forum of Researchers and Lecturers, 2024)
Problem/Background (GAP): Building Construction Permit is a permit granted by the City/Regency Government to building owners to modify, build new, reduce and maintain buildings in accordance with administrative requirements and technical requirements. In its implementation, the aim of the IMB is to create an orderly layout and layout that is in accordance with the land use designation so that it will create harmony and balance between the environment and the building. To optimize public services to the community in the licensing sector which utilizes advances in information technology, the Boyolali Regency Investment and One-Stop Integrated Services Service has used a regionally managed online service system known as PTSP Online. This online service system was only implemented in 2020, where previously the Construction Building Permit (IMB) processing service was still carried out manually or offline. With this site, it is hoped that the quality of IMB licensing services can be improved more quickly and effectively. Objective: The purpose of this research is to determine and analyze the implementation of online-based Building Permit service policies and to determine the obstacles that occur in online-based Building Permit services. Method: The research design used in this research is qualitative research using descriptive methods and a deductive approach. Data collection techniques use interviews and documentation. Then the data collected was analyzed using data reduction techniques, data presentation and drawing conclusions. Results/Findings: The results of this research indicate that the implementation of the online building permit service policy in Boyolali Regency, Central Java Province has not been optimal because there are still obstacles in implementing the policy such as lack of socialization and information about online IMB regulations, the technology used is not optimal, lack of a technical team In the field, there are still brokers in online IMB processing. Conclusion: Based on the research conducted, the author suggests to DPMPTSP Boyolali Regency to carry out scheduled socialization so that the community is able to understand existing policies, increase supervision so that brokering practices are minimized, carry out repairs and maintenance of network systems, and recruit a team of technical employees.